Tanks and armored fighting vehicles visual encyclopedia (Amber Books, 2009)
A directory of more than 1000 of the finest tanks, jeeps, trucks, tank destroyers, wheeled and tracked infantry vehicles, amphibious vehicles, engineer vehicles, self propelled artillery and armoured cars. It is of interest to followers of modern military history or land warfare.